Table of Content - - (Journal of Humanities & Social Sciences, 2024)
Table of Content 1. Family Problems of Heart Patients, and the Medical Social Worker’s Role Facing Them A study applied to a sample of heart patients in Al-Madinah Al-Munawwarah Hospitals Researcher / Amna Ahmed Abdullah Harmoush 2. Methods of Activating the Professional Role of the Social Worker in the Medical Sector: An Applied Study on Social Workers in Government Hospitals in Jeddah Researcher / Abdullah Abdulrahman Al-Qarni, Prof. Dr. Abdulrahman Abdullah Al-Omari 3. The Indications of the Environmental in Wadi Al Ajradi in the Imam Turki bin Abdullah Reserve During the Holocene Period. Dr. Maha Awwad Alanazi 4. The Role of Metamorphosis in Arabic Children’s Literature Dr. Rafi’ Saed Yahya